Nutraceutical compounds: Echinoids, flavonoids, xanthones and caffeine identified and quantitated in the leaves of Coffea arabica trees from three regions of Brazil - Almeida, Ricardo Farias de; Breuer, Andrea; Ulrich, Cornelia; Owen, Robert (Food research international, 2019)
There are relatively few studies concerning the use of coffee leaves for medicinal purposes and the composition of secondary plant substances. Therefore, we identified and quantitated polyphenolic compounds along with caffeine present in methanol extracts of Coffea arabica leaves from three different regions of Brazil (Ceará, Minas Gerais and São Paulo) by HPLC-ESI-MS. In addition, correlations between polyphenolic content of the coffee leaves and antioxidant assays DPPH, FRAP and ORAC were evaluated. Fifteen compounds belonging to three classes of polyphenols (xanthones, chlorogenic acids and flavonoids) along with the alkaloid caffeine were detected. The mean concentration of total polyphenolic compounds in the leaves of C. arabica, harvested from three different regions of Brazil was quite variable. The highest values were detected in the coffee leaves harvested in Minas Gerais (n=4) at 40.80(13.00) g/kg (SD), followed by coffee leaves harvested in São Paulo (n=20) at 24.79(20.19) g/kg, and the lowest in coffee leaves harvested in Ceará (n=11) in the Northeast of Brazil at 10.30(5.61) g/kg. The three classes of polyphenols, all showed excellent correlations in the antioxidant assays. Coffee leaf tea, appears to be an excellent functional beverage, with its high content of polyphenolic compounds, which may render positive biologic effects, when inbibed as part of the normal human diet.